Effect of Huoxiang Zhengqi Pill on Early Neurological Deterioration in Patients with Acute Ischemic Stroke Undergoing Recanalization Therapy and Predictive Effect of Essen Score. (9th September 2020) - Huang, Zhi-Xin; Lin, Jianguo; Zhang, Cheng; Dai, Ying-Yi; Lin, Songbin; Liu, Xintong
Abstract : Early neurologic deterioration (END) in the acute phase of ischemic stroke is a serious clinical event, which is closely related to poor prognosis. Therefore, it is important to identify presentation features that predict END and take relevant treatment measures, as they could help to prevent the deterioration of high-risk patients. The prospective intervention study was carried out from January 2018 to December 2019. We included consecutive patients hospitalized for acute ischemic stroke (AIS) within 6 hours of onset. Patients were randomly assigned (1 : 1) to recanalization therapy plus Huoxiang Zhengqi Pill (HXZQ) (intervention group) or standard recanalization therapy alone (control group). The primary outcome was the development of END according to predefined criteria within the first 1 week of stroke onset. Poisson regression was used to identify predictors for END. Of the 155 patients enrolled in the study (age, 63 ± 11 years; 28.4% female), 20 (12.9%) developed END. Univariate analysis showed that the use of HXZQ and Essen stroke risk score (ESRS) (low risk group) were protective factors for END, while advanced age was a risk factor for END. However, in multivariate analysis, only ESRS (OR, 0.232; 95%CI, 0.058–0.928; P = 0.039 ) and the use of HXZQ (OR, 0.297; 95%CI, 0.096–0.917; P = 0.035 ) were statistically significant. ESRS can be used as the prediction factor of END. HXZQ has small side effects and wide indication. It could be used in the treatment of AIS.